A new approach for the quantification of synchrony of multivariate non-stationary psychophysiological variables during emotion eliciting stimuli - Kelava, Augustin; Muma, Michael; Deja, Marlene; Dagdagan, Jack Y.; Zoubir, Abdelhak M. (Frontiers in Psychology, 2015)
Emotion eliciting situations are accompanied by reactions on multiple response variables on subjective, physiological, and behavioral levels. The quantification of the overall simultaneous synchrony of psychophysiological reactions, plays a major role in emotion theories and has received increasing attention in recent research. From a psychometric perspective, the reactions represent multivariate non-stationary intra-individual time series. In this paper, we present a new time-frequency based latent variable approach for the quantification of the synchrony of the responses. The approach is applied to empirical data collected during an emotion eliciting situation. The results are compared with a complementary inter-individual approach of Hsieh et al. (2011). Finally, the proposed approach is discussed in the context of emotion theories, and possible future applications and limitations are provided.